Phenotypic and Genotypic Detection of Metallo-b Lactamase in Non-Fermenting Gram Negative Bacilli Obtained from Clinical Samples in a Tertiary Care Hospital in Nepal - Sapkota, Jyotshna; GC, Divya Shree; Adhikari, Ram Prasad; Khadka, Shusila; Pandey, Ritu; Sah, Anil Kumar; Khanal, Laxmi Kant (Journal of Institute of Medicine Nepal, 2025)
Introduction Non-fermenting Gram-negative bacilli, including Pseudomonas aeruginosa and Acinetobacter baumannii, are significant nosocomial pathogens with limited treatment options due to their intrinsic and acquired resistance mechanisms. Among these, metallo-β-lactamases are of major concern which hydrolyze carbapenems and contribute to antimicrobial resistance. This study aimed to determine the prevalence of Metallo-β-Lactamase-producing non-fermenting gram negative bacilli in clinical specimens using both phenotypic and genotypic methods. Methods A descriptive cross-sectional study was conducted at Nepal Medical College Teaching Hospital from January 2024 to December 2024. A total of 16,954 clinical specimens were processed for culture and sensitivity testing. NFGNB were identified using standard microbiological methods. Antimicrobial susceptibility testing was conducted using the Kirby-Bauer disk diffusion method following Clinical and Laboratory Standards Institute guidelines. MBL production was detected phenotypically using the Imipenem-EDTA combined disc method. The presence of IMP and VIM genes was confirmed by conventional PCR. Results Among 16,954 specimens, 163 (0.96%) NFGNB isolates were identified, with Pseudomonas aeruginosa (52.1%) being the most prevalent, followed by Acinetobacter species (39.3%) and Burkholderia species (8.6%). MBL production was detected in 22 (13.5%) isolates: Pseudomonas aeruginosa (59.1%), and Acinetobacter species (40.9%). Genotypically IMP and VIM genes were found in 36.4% and 31.8% of MBL-positive isolates, respectively, while one isolate harbored both genes. Notably, 27.3% of phenotypic MBL producers tested negative for both IMP and VIM, suggesting the potential involvement of other MBL genes. Conclusion The significant prevalence of MBL-producing NLFGNB, particularly among Pseudomonas aeruginosa and Acinetobacter species, highlights a serious challenge for antimicrobial therapy and underscores an urgent need for robust infection control and antimicrobial stewardship strategies.